Effect of nitrogen atom positioning on the trade-off between emissive and photocatalytic properties of carbon dots. Issue 1 (December 2017) - Bhattacharyya, Santanu; Ehrat, Florian; Urban, Patrick; Teves, Roland; Wyrwich, Regina; Döblinger, Markus; Feldmann, Jochen; Urban, Alexander; Stolarczyk, Jacek
Abstract Carbon dots (CDs) are a versatile nanomaterial with attractive photoluminescent and photocatalytic properties. Here we show that these two functionalities can be easily tuned through a simple synthetic means, using a microwave irradiation, with citric acid and varying concentrations of nitrogen-containing branched polyethyleneimine (BPEI) as precursors. The amount of BPEI determines the degree of nitrogen incorporation and the different inclusion modes within the CDs. At intermediate levels of BPEI, domains grow containing mainly graphitic nitrogen, producing a high photoluminescence yield. For very high (and very low) BPEI content, the nitrogen atoms are located primarily at the edge sites of the aromatic domains. Accordingly, they attract photogenerated electrons, enabling efficient charge separation and enhanced photocatalytic hydrogen generation from water. The ensuing ability to switch between emissive and photocatalytic behavior of CDs is expected to bring substantial improvements on their efficiency for on-demand light emission or energy conversion applications. Carbon dots are an emergent class of nanomaterials that hold promise for innovations in imaging, sensing, and catalytic technologies. Here, Stolarczyk and colleagues control the nitrogen-atom content and location within carbon dots, reporting the resulting impact on emissivity and photocatalytic behaviour.